(untitled) (FAVE Sección Ciencias Veterinarias, 2022)
Cold stress in calves can be very detrimental to their health and performance. The aim of this work was to evaluate the effect of artificial rearing management conditions and their relationship to cold stress in dairy calves. A total of 160 calves were evaluated during the early morning hours and it was recorded whether or not the animals had cape and whether or not they had bed in pens. Also, it was observed if they had protection for climatic limitations. Rectal temperature and whether or not they were shivering were also recorded. Calves with rectal temperature equal to or lower than 37.2 °C were considered to be in cold stress. The statistical analysis of the data was performed using the non-parametric Chi-square test and the probability of occurrence was calculated using Odds Ratio. It was found that calves under stress conditions were 4.93 times more likely to shiver; that having bed in pens was favorable for preventing stress (0.027), that plastic cape increased the probability of suffering from stress (0.006) and that providing shelter to animals had a positive effect on the prevention of cold stress (p = 0.027) in dairy calves.